Optimization Design for Reliability of the Oscillating Follower Disk Cam Mechanism Based on Improved Hunter-Prey Optimization Algorithm - Chao Wang; Wei Peng (IEEE Access)
Cam mechanism is widely used in engineering designs such as engines, presses and gear-cutting machines because of its advantages including high transmission efficiency, high reliability, and the ability to realize complex motions. To quantify the negative effects of dimension error, clearance error of kinematic pair and wear error of cam higher pair on the motion accuracy of oscillating follower disk cam mechanism, a computing model of motion reliability and reliability sensitivity of oscillating follower disk cam mechanism was established. By analyzing the reliability sensitivity, we find that the distance error between the camshaft axis and the swing center are two significant factors for the motion reliability of cam mechanism. To maximize the motion reliability of the mechanism, an improved Hunter Prey Optimization (IHPO) algorithm was proposed to identify the optimal dimensional parameters of the oscillating follower disk cam mechanism. The simulation results show that the presented method has desirable applicability for improving the motion reliability of disk cam mechanism, and provides a certain reference for the design of other cam mechanisms.